LO057: Association between metoclopramide treatment in the ED for concussion and persistent post-concussion headaches: a propensity score matching analysis. (2nd June 2016) - Bresee, N.; Aglipay, M.; Barrowman, N.; Momoli, F.; Dubrovsky, A.; Zemek, R.
Abstract : Introduction: There is a paucity of pediatric literature regarding effective treatment for post-concussion headache. The objective of this study was to assess whether metoclopramide treatment in the Emergency Department (ED) within 48 hours of injury was associated with reduced persistent headache symptoms post-concussion at 1-week and 1-month post-injury.Methods: Children aged 8-18 years with acute concussion were enrolled across 9 EDs of the Pediatric Emergency Research Canada network in a prospective cohort study [Predicting and Preventing Post-concussive Problems in Paediatrics (5P)] from August 2013 to June 2015. Treatments administered in ED (including metoclopramide) were collected using standardized forms. Self-report symptom questionnaires were rated at baseline, at 7 and 28 days follow-up using the validated Post-Concussion Symptom Inventory (PCSI). Propensity scores for treatment with metoclopramide were calculated using a multivariate logistic regression model including confounders. Intervention and control groups were matched 1:4 on the logit of the propensity scores using a greedy algorithm and nearest-neighbour approach. The primary outcome was headache persistence at one-month.Results: 2095 patients met inclusion criteria and completed baseline assessment. At 1 and 4 weeks respectively, 54% (963/1808) and 26% (456/1780) of participants completing follow-up had persistent headache symptoms. 50 metoclopramide treated participants were propensity score matched to 234 controls (1:4 matching). At 4 weeks, no statistically significant difference in persistent headache symptoms was observed between the treatment and propensity score matched control groups (OR: 0.67; 95% CI: 0.33-1.36, p=0.26). There was also no statistically significant difference between the groups at 1-week post-concussion (OR 0.58; 95% CI: 0.32-1.05, p=0.07).Conclusion: This secondary analysis was unable to detect a statistically significant association between acute ED treatment with metoclopramide and reduced medium and long-term headache symptoms post-concussion. Nevertheless, the 1-week results hold promise, but require a well-powered RCT to fully address confounding issues to determine the benefit of metoclopramide post-concussion.